Traditional Uses of Medicinal Plants by The Magar Community of Pokhara Metropolitan City - Lamichane, Yojana; Dwa, Om Prasad (Kalika Journal of Multidisciplinary Studies, 2024)
Most people still widely use medicinal plants for their primary health care needs in Nepal. Ethnomedicinal studies play a key role in conserving traditional knowledge and its use. This current research was conducted to document the medicinal plants used by the Magar community for various disease ailments among the selected wards of Pokhara Metropolitan City. This study uses both primary and secondary data. The primary data were collected through field visits, group discussions, and interviews using a semi-structured questionnaire. Altogether 101 medicinal plant species belonging to 55 families and 89 genera have been recorded. The dominant family was Asteraceae having 9 species. Herbs (37 species) were the most used life form of the plant while rhizomes (33 species), were the most used plant part.The most favored mode of drug preparation was found to be paste form (31 species). The highest number of plants were used for gastrointestinal disorders. The indigenous knowledge of lesser-known plants is rapidly decreasing. Therefore, necessary efforts should be taken by the federal, provincial, and local governments for the conservation and sustainable use of medicinal plants.